Oral Pathogens and Their Antibiotics from Marine Organisms: A Systematic Review of New Drugs for Novel Drug Targets - Sehyeok Im; Jun Hyuck Lee; Youn-Soo Shim (The Korean Society of Dental Hygiene Science, 2024)
Background: Recent studies have elucidated the quorum-sensing mechanisms, biofilm formation, inter-pathogen interactions, and genes related to oral pathogens. This review aims to explore the recent expansion of drug targets against oral pathogens and summarize the current research on novel antibiotic substances derived from marine organisms that target oral pathogens. Methods: A comprehensive literature review summarized the novel mechanisms pertaining to quorum-sensing signal transmission systems, biofilm formation, and metabolite exchange in oral pathogens. The amino acid sequences of the 16 proteins identified as potential drug targets were systematically classified and compared across various oral microorganisms. Results: Through a literature review, we identified nine studies researching quorum sensing signaling inhibitors targeting oral pathogens. A comparison of the amino acid sequences of 16 potential drug targets in oral microorganisms revealed significant differences between oral pathogens and beneficial oral symbiotic microorganisms. These findings imply that it is possible to design drugs that can bind more selectively to oral pathogens. Conclusion: By summarizing the results of recent research on the signaling mechanisms that cause pathogenicity, new drug targets against oral pathogens were proposed. Additionally, the current status of developing new antibiotics for oral pathogens using recently developed quorum sensing inhibitors and natural products derived from marine organisms was introduced. Consequently, marine natural products can be used to develop drugs targeting new proteins in oral pathogens.